Review papersLegal issues regarding HIV infection and AIDS disease - Jakubowicz, Jędrzej; Jakubowicz, Oliwia; Żaba, Czesław; Żaba, Ryszard; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
This paper presents an analysis of regulations connected with HIV infection and AIDS disease, as well as regulations indirectly connected with the clinical problems mentioned above. This article is connected with derogation of the previous and implementation of the new bill from 5th of December 2008 on preventing and combating human infections and infectious disease.